Diversity of Rainbow Trout Blood B Cells Revealed by Single Cell RNA Sequencing - Pedro Perdiguero; Esther Morel; Carolina Tafalla (Biology, 2021)
Single-cell sequencing technologies capable of providing us with immune information from dozens to thousands of individual cells simultaneously have revolutionized the field of immunology these past years. However, to date, most of these novel technologies have not been broadly applied to non-model organisms such as teleost fish. In this study, we used the 10× Genomics single cell RNA sequencing technology and used it to analyze for the first time in teleost fish the transcriptional pattern of single B cells from peripheral blood. The analysis of the data obtained in rainbow trout revealed ten distinct cell clusters that seem to be associated with different subsets and/or maturation/differentiation stages of circulating B cells. The potential characteristics and functions of these different B cell subpopulations are discussed on the basis of their transcriptomic profile. The results obtained provide us with valuable information to understand the biology of teleost B cells and offer us a repertoire of potential markers that could be used in the future to differentiate trout B cell subsets.